IMPACT OF ENERGY CONSUMPTION AND ENVIRONMENTAL DEGRADATION ON ECONOMIC GROWTH IN BANGLADESH - Alam, Md. Mahbub; Hassan, Mohamad Ghozali; Sadekin, Md. Nazmus (CENTRAL ASIA AND THE CAUCASUS, 2021)
The main objectives of this study are to examine the impact of energy consumption and environmental degradation (CO2 emissions) on economic growth in Bangladesh covering the periods of 1972 to 2018 by employing the Johansen cointegration test, VECM approach, and Granger causality test. The Johansen cointegration result indicates that gross capital formation (GCF), labor, Electricity power consumption (EPC), energy consumption (EC) has a positive and statistically significant effect on economic growth (RGDP) while environmental degradation (carbon dioxide emissions) has an inverse effect on it. The results of VECM show that there exist a long-run causal nexus among the variables and there is short-run causality running from the capital formation and electricity power consumption to the economic growth while there is no short-run causality from the labor, energy consumption, carbon emission to the economic growth. The causality test shows that there exist a unidirectional causal relationship from economic growth to labor, EPC to RGDP, GCF to labor, EC to GCF, carbon emissions (CO2) to GCF, labor to EPC, EC to labor, CO2 to labor, and carbon emissions to EPC and a bi-directional causal nexus between GCF and RGDP; GCF and labor; EPC and carbon emission in Bangladesh. However, the study suggests that a huge change of low carbon advancements like renewable energy and energy sufficiency may contribute to decrease emissions and thus support the long-run economy.